Konseling untuk mengurangi inferioritas pada pasien skizofrenia - Riski januar triharsari (Universitas Muhammadiyah Malang, 2021)
Schizophrenia is a thought disorder that is not interconnected, the presence of erroneous perceptions, ﬂat affect, withdrawal from the social environment, and failed functioning of life. This study examines the effect of Adlerian counseling to reduce feelings of inferiority in Schizophrenic patients. The assessment method used in this study is interview, observation, psychological tests namely Graphics Test, SSCT, WWQ, TAT, and WAIS. The intervention was given using counseling with the Adler approach which consisted of nine sessions. The results of the intervention showed that the inferior subject could be reduced, which was indicated by no longer being ashamed to talk to women, being able to ﬁnd an understanding that he had implemented the wrong lifestyle all this time. Subjects also become more active.